Anti-tumor activity of selective inhibitors of XPO1/CRM1-mediated nuclear export in diffuse malignant peritoneal mesothelioma: the role of survivin - De Cesare, Michelandrea (Oncotarget, 2015)
Survivin, which is highly expressed and promotes cell survival in diffuse malignant peritoneal mesothelioma (DMPM), exclusively relies on exportin 1 (XPO1/CRM1) to be shuttled into the cytoplasm and perform its anti-apoptotic function. Here, we explored the efficacy of Selective Inhibitors of Nuclear Export (SINE), KPT-251, KPT-276 and the orally available, clinical stage KPT-330 (selinexor), in DMPM preclinical models. Exposure to SINE induced dose-dependent inhibition of cell growth, cell cycle arrest at G1-phase and caspase-dependent apoptosis, which were consequent to a decrease of XPO1/CRM1 protein levels and the concomitant nuclear accumulation of its cargo proteins p53 and CDKN1a. Cell exposure to SINE led to a time-dependent reduction of cytoplasmic survivin levels. In addition, after an initial accumulation, the nuclear protein abundance progressively decreased, as a consequence of an enhanced ubiquitination and proteasome-dependent degradation. SINE and the survivin inhibitor YM155 synergistically cooperated in reducing DMPM cell proliferation. Most importantly, orally administered SINE caused a significant anti-tumor effect in subcutaneous and orthotopic DMPM xenografts without appreciable toxicity. Overall, we have demonstrated a marked efficacy of SINE in DMPM preclinical models that may relay on the interference with survivin intracellular distribution and function. Our study suggests SINE-mediated XPO1/CRM1 inhibition as a novel therapeutic option for DMPM.